Methyl esters selectivity of transesterification reaction with homogenous alkaline catalyst to produce biodiesel in batch, plug flow, and continuous stirred tank reactors - Nasir, N. F.; W. Daud, W. R.; Kamarudin, S. K.; Yaakob, Z. (Hindawi Publishing Corporation, 2014)
Selectivity concept is essential in establishing the best operating conditions for attaining maximum production of the desired product. For complex reaction such as biodiesel fuel synthesis, kinetic studies of transesterification reaction have revealed the mechanism of the reaction and rate constants. The objectives of this research are to develop the kinetic parameters for determination of methyl esters and glycerol selectivity, evaluate the significance of the reverse reaction in transesterification reaction, and examine the influence of reaction characteristics (reaction temperature, methanol to oil molar ratio, and the amount of catalyst) on selectivity. For this study, published reaction rate constants of transesterification reaction were used to develop mathematical expressions for selectivities. In order to examine the base case and reversible transesterification, two calculation schemes (Case 1 and Case 2) were established. An enhanced selectivity was found in the base case of transesterification reaction. The selectivity was greatly improved at optimum reaction temperature (60 C), molar ratio (9 : 1), catalyst concentration (1.5 wt.%), and low free fatty acid feedstock. Further research might explore the application of selectivity for specifying reactor configurations.